Solving Fuzzy Multi-Objective Linear Programming Problems with Non Linear Membership Function Using Artificial Neural Networks - Elsharkawy, Khaled (International Journal of Advanced Science and Technology, 2019)
Fuzzy multi-objective linear programming problems (FMLOPP) have many applications in the field of science and engineering. In this paper, (FMOLPP) we studied the Cost factors to be fuzzy with non- linear membership function, then we compare the time of solution with the algebraic approach which proposed to solve the above problem using the technique proposed and between the solution using trained feed forward artificial neural networks (FFANN). Keywords: Multi-Objective Linear Programming, Fuzzy Multi-Objective Linear Programming Problems, Feed Forward Artificial Neural Networks, Decision Making, Multi-Objective Mixed Non-Linear Programming Problem.